ANALISIS PERATURAN HAK DAN KEWAJIBAN PARA PIHAK ATAS PESANAN COD (CASH ON DELIVERY) PADA APLIKASI SHOPEE - NIM: A1011211301, ELSI MAHARANI (Jurnal Fatwa Hukum, 2025)
AbstractThe COD payment system often causes losses for businesses, particularly related to payment cancellations by buyers. This study aims to analyze the regulations regarding the rights and obligations of the parties in electronic commerce (e-commerce) transactions with the Cash on Delivery (COD) payment system through the Shopee app, as well as the legal protection provided against COD payment cancellations. This study uses a juridical-sociological approach, focusing on the regulations related to e-commerce and consumer protection. The data used includes primary legal materials (legislation and interviews), secondary legal materials (books and expert opinions), and tertiary legal materials (dictionaries, encyclopedias, and related articles). Data collection was conducted through library research, with qualitative data analysis to address the research problems. Legal regulations concerning e-commerce do not specifically regulate payments using COD but refer to Article 69 of the E-Commerce Government Regulation. Cash on Delivery is a payment method made when the goods are received by the buyer. This presents a risk for the seller because the goods must be shipped before payment is received, which can result in losses if the buyer refuses to pay. The Indonesian government, through Government Regulation No. 80 of 2019, regulates the obligations of businesses in online transactions, including COD transactions. Since October 14, 2024, Shopee has implemented new rules to protect COD transactions. If an order fails to be delivered, the goods will be returned to the seller. COD will be temporarily deactivated if the buyer cancels the order twice within 60 days. The seller has 7 days to confirm the condition of the goods once returned. If damaged, the seller must submit photo evidence. If the buyer is at fault, the seller will receive a refund. For Reguler and Hemat shipping, damage or loss of goods will be compensated 10 times the shipping cost or up to IDR 1,000,000, while Instant shipping claims can reach up to IDR 10,000,000. With these regulations, protection for parties in COD transactions through Shopee has improved.Keywords: E-Commerce, Cash on Delivery (COD), Legal Protection, Shopee, Payment Cancellation.    AbstrakSistem pembayaran COD sering menimbulkan kerugian bagi pelaku usaha, terutama terkait pembatalan pembayaran oleh Pembeli. Penelitian ini bertujuan untuk menganalisis peraturan hak dan kewajiban para pihak dalam transaksi jual beli elektronik (e- commerce) dengan sistem pembayaran Cash on Delivery (COD) melalui aplikasi Shopee serta perlindungan hukum yang diberikan terhadap pembatalan pembayaran COD. Penelitian ini menggunakan pendekatan yuridis Sosiologis dengan fokus pada peraturan perundang-undangan terkait E-Commerce dan perlindungan konsumen. Data yang digunakan terdiri dari bahan hukum primer (peraturan perundang-undangan dan wawancara), bahan hukum sekunder (buku, dan pendapat ahli), serta bahan hukum tersier (kamus, ensiklopedia, dan artikel terkait). Teknik pengumpulan data dilakukan melalui penelitian kepustakaan (library research), dengan analisis data dilakukan secara kualitatif untuk menjawab permasalaham dalam penelitian. Aturan hukum tentang E-commerce tidak mengatur secara khusus pembayaran dengan COD, namun mengacu pada Pasal 69 PP E-Commerce. Cash on delivery merupakan metode pembayaran yang dilakukan pada saat barang telah diterima oleh pembeli,   Hal ini memiliki risiko bagi penjual, karena barang harus dikirim terlebih dahulu sebelum pembayaran diterima, yang dapat menyebabkan kerugian jika pembeli menolak membayar. Pemerintah Indonesia melalui Peraturan Pemerintah No. 80 Tahun 2019 mengatur kewajiban pelaku usaha dalam perdagangan daring, termasuk transaksi COD. Sejak 14 Oktober 2024, Shopee menerapkan peraturan baru untuk melindungi transaksi COD. Jika pesanan gagal dikirim, barang akan dikembalikan ke penjual. COD akan dinonaktifkan jika pembeli membatalkan pesanan 2 kali dalam 60 hari. Penjual punya 7 hari untuk mengonfirmasi keadaan barang setelah dikembalikan. Jika rusak, penjual harus mengirim bukti foto. Jika kesalahan di pihak pembeli, penjual mendapat pengembalian uang. Untuk pengiriman Reguler dan Hemat, kerusakan atau kehilangan barang diganti 10 kali ongkos kirim atau maksimal Rp1.000.000, sedangkan pengiriman Instant klaim bisa mencapai Rp10.000.000. Dengan aturan ini, perlindungan untuk pihak dalam transaksi COD melalui Shopee semakin baik.Kata kunci: E-Commerce, Cash On Delivery (COD), Perlindungan Hukum, Shopee, Pembatalan Pembayaran.